The biological variation of serum 1,25-dihydroxyvitamin D and parathyroid hormone, and plasma fibroblast growth factor 23 in healthy individuals - Iannone, Francesca; Angotti, Elvira; Lucia, Fortunata; Martino, Luisa; Antico, Giulio Cesare; Galato, Francesco; Aversa, Ilenia; Gallo, Raffaella; Giordano, Caterina; Abatino, Antonio; Mancuso, Serafina; Carinci, Lorenza Giaquinto; et al. (Clinica chimica acta, 2024)
•Measuring 1,25(OH)2D, PTH 1–84 and intact FGF23 is crucial for diagnosing a variety of diseases affecting bone and mineral homeostasis.•This study provides for the first time the biological variability estimates of 1,25(OH)2D.•This study also consolidates the biological variability data for intact FGF23, and PTH 1–84.•For accurate clinical interpretation of these biomarkers, it is crucial to consider the individual clinical context rather than relying solely on population-based reference intervals. Measuring 1,25-dihydroxyvitamin D (1,25(OH)2D), parathyroid hormone 1–84 (PTH 1–84) and intact FGF23 (iFGF23) is crucial for diagnosing a variety of diseases affecting bone and mineral homeostasis. Biological variability (BV) data are important for defining analytical quality specifications (APS), the usefulness of reference intervals, and the significance of variations in serial measurements in the same subject. The aim of this study was to pioneer the provision of BV estimates for 1,25(OH)2D and to improve existing BV estimates for iFGF23 and PTH 1–84. Serum and plasma-EDTA samples of sixteen healthy subjects have been collected for seven weeks and measured in duplicate by chemiluminescent immunoassay on the DiaSorin Liaison platform. After variance verification, within-subject (CVI) and between-subject (CVG) BV estimates were assessed by either standard ANOVA, or CV-ANOVA. The APSs were calculated according to the EFLM-BV-model. We found the following CVI estimates with 95% confidence intervals:1,25(OH)2D, 22.2% (18.9–26.4); iFGF23, 16.1% (13.5–19.5); and PTH 1–84, 17.9% (14.8–21.8). The CVG were: 1,25(OH)2D, 21.2% (14.2–35.1); iFGF23, 21.1% (14.5–35.8); and PTH 1–84, 31.1% (22.1–50.8). We report for the first time BV estimates for 1,25(OH)2D and enhance existing data about iFGF23-BV and PTH 1–84-BV through cutting-edge immunometric methods.